Pancreaticobronchial Fistula: A Complication of Acute Pancreatitis - Overbeck-Zubrzycka, Dorota; Lochan, Rajiv J; Balupuri, Shlok; Jackson, Ralph W; Charnley, Richard M (JOP. Journal of the Pancreas, 2011)
Context Pancreaticobronchial fistula is a rare complication of severe pancreatitis. Various diagnostic methods have been described previously. Case report The presentation, diagnostic methods, management and 5-year follow-up of a 40-year-old woman with severe gallstone induced pancreatitis complicated by a pancreaticobronchial fistula were reviewed. Diagnosis was made on the endotracheal intubation when amylase rich-fluid was drained via the tube and confirmed by CT scanning. Successful management was achieved by an open pancreatic necrosectomy, during which air bubbles were seen emerging from the pancreatic collection which supported the diagnosis of the fistula. Five-year follow-up did not reveal any complications. Conclusions Pancreaticobronchial fistulas have the potential to cause severe respiratory complications and mortality. Awareness of this condition is important in the treatment of complicated cases of pancreatitis. Image: 3-dimentional reconstruction of the pancreaticobronchial fistula.